Transformasi Pendidikan Islam di Mesir: Studi Pemikiran Muhammad Abduh - Lintang Hikmah Pratiwi; Dyah Nur Rachmah (Yayasan Al-Afif, 2026)
At the end of the 19th century, Islamic education in Egypt faced a severe intellectual crisis marked by the dominance of taqlid culture, knowledge dichotomy, and passive teaching methods based solely on rote memorization. This study aims to critically analyze Muhammad Abduh's thought in the context of Islamic education transformation in Egypt, examining the historical background that shaped his ideas, the core principles of his educational reform, and their relevance to the development of modern Islamic education. This research employs a qualitative literature study method, collecting and analyzing data from relevant academic sources. The findings reveal that Abduh's reform vision encompassed three pillars: curriculum integration of religious and modern sciences, transformation of pedagogical methods from transmission to critical inquiry, and the empowerment of women through education. His reforms at Al-Azhar and Dar al-Ulum became a foundational blueprint for Islamic educational modernization globally, including in Indonesia.